MULTISTORY FRAMED BUILDINGS WITH SLAB CAST OVER PRECAST JOISTS: RECOMMENDATIONS FOR DESIGNING CONCRETE ELEMENTS KEY JOINTS - Dovzhenko, O. O.; Pogribnyi, V. V.; Chursa, Yu. V.; Chernenko, Ya. V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The role of joints which are used to provide interoperability of separate elements in prefabricated monolithic frame design systems with flat slabs was researched. Special attention is paid to key joints that are exposed to significant shear strength and provide the structures’ solidity during the operation. On the basis of the experimental studies, recommendations for the joints design are suggested. In Poltava National Technical University a key joints calculation method has been developed, which considers the damage nature, a set of determining impact factors and is recommended for extensive use.
Keywords: precast-and cast-in situ structural system; joint; key; strength; plasticity; cut